Currents associated with Saturn's intra-D ring azimuthal field perturbations - Hunt,G; Cowley,S; Provan,G; Cao,H; Bunce,E; Dougherty,M; Southwood,D (Journal of Geophysical Research: Space Physics, 2019)
During the final 22 full revolutions of the Cassini mission in 2017, the spacecraft passed at periapsis near the noon meridian through the gap between the inner edge of Saturn’s D ring and the denser layers of the planet’s atmosphere, revealing the presence of an unanticipated low-latitude current system via the associated azimuthal perturbation field peaking typically at ~10-30 nT. Assuming approximate axisymmetry, here we use the field data to calculate the associated horizontal meridional currents flowing in the ionosphere at the feet of the field lines traversed, together with the exterior field-aligned currents required by current continuity. We show that the ionospheric currents are typically~0.5–1.5 MA per radian of azimuth, similar to auroral region currents, while the field-aligned current densities above the ionosphere are typically ~5-10 nA m-2 , more than an order less than auroral values. The principal factor involved in this difference is the ionospheric areas into which the currents map. While around a third of passes exhibit unidirectional currents flowing northward in the ionosphere closing southward along exterior field lines, many passes also display layers of reversed northward field-aligned current of comparable or larger magnitude in the region interior to the D ring, which may reverse sign again on the innermost field lines traversed. Overall, however, the currents generally show a high degree of north-south conjugacy indicative of an interhemispheric system, certainly on the larger overall spatial scales involved, if less so for the smaller-scale structures, possibly due to rapid temporal or local time variations.